Histopathological Reporting of Actinomyces Colonies in Tonsils-Utility or Futility? A Retrospective Study - KALPANA SHARMA (JCDR Research and Publications Private Limited, 2021)
Introduction: Actinomyces colonies in tonsillectomy specimens are often ignored as commensals and histopathology reports do not carry any information about them. But evidence suggests that under favourable conditions these may become invasive and pathogenic, serving as precursors to later systemic disease. Early identification of mucosal breach by these bacteria may have a role in the clinical management and future prognosis. Aim: To determine the frequency of occurrence of Actinomyces colonies in tonsillectomy specimens and study the various associated histological alterations which may provide a clue to their pathogenicity. Materials and Methods: This was a retrospective study on 140 tonsillectomy specimens, from 70 patients who had undergone elective, bilateral tonsillar surgery. Tonsils were examined for Actinomyces colonies and histological alterations as per two different grading criteria. Different clinicopathological features were associated, those with and without Actinomyces colonies using appropriate statistical tools (t-test, Chi-square and Fisher’s exact test; Statistical Package for the Social Sciences SPSS version 23.0). Results: A total of 140 tonsillar tissue specimens were analysed from 70 patients and divided into two groups Group 1 (with actinomycosis) and Group 2 (without actinomycosis) with a mean age of 13.6±6.63 years and 11.8±7.19 years, respectively. The frequency of Actinomyces colonies was found to be 40% (28 of 70 patients) with bilateral presence in 28.5% (8 of 28 patients). Tissue reaction was present in 36.11% (13/36 tonsillar specimens) of the tonsillectomy specimens harbouring Actinomyces. Deeply situated colonies elicited tissue reaction more frequently (11/19 tonsillar specimens; 57.89%) compared to superficial ones (2/17 tonsillar specimens; 11.76%). Tonsillar cryptitis was the most statistically significant histopathological finding associated with the presence of Actinomyces colonies (p=0.029). Conclusion: Tonsillar cryptitis was found to be a consistent histological finding in tonsillar actinomycosis. The frequent acute inflammatory responses generated by deeply located Actinomyces colonies refutes their role as mere commensals. It is suggested that tonsil histopathology reports should mention the presence/ location/ tissue reaction surrounding Actinomyces colonies to differentiate mere colonisation from invasion. This could have profound clinical implications in terms of necessity of antibiotic use for prophylaxis/ and or treatment.